Chapter La comunicazione istituzionale dell'Università tra semplificazione linguistica e strategie possibili per un linguaggio inclusivo - Di Valvasone, Luisa (Proceedings e report, 2023)
The article explores gender-neutral language strategies in Italian university documents, introducing "gender obfuscation" to avoid gender markers. Strategies discussed include using generic nouns, passive/impersonal verbs, and relative/indefinite pronouns. Inclusive language benefits are acknowledged, but complexity and reduced clarity are highlighted. The authors recommend inclusive language, including the unmarked masculine form for complex cases. Italian universities adoption of Gender Equality Plans (GEP) in response to European Commission directives is also discussed. Emphasis is placed on language attention in GEPs and collaboration with linguists for inclusivity and gender equality. Balancing language simplification with gender-inclusive objectives is recognized as a challenge.